2002
DOI: 10.1002/pen.11128
|View full text |Cite
|
Sign up to set email alerts
|

A new concept of active temperature control for an injection molding process using infrared radiation heating

Abstract: This paper deals with an innovative injection molding process that uses infrared radiation heating for active temperature control of the molded polymer. The feasibility of the proposed technique was investigated through numerical simulation and experimental study. By directly heating the molded polymer with radiation energy, precise and rapid temperature control and a small effect on the cooling duration were expected. Zinc‐selenide and a CO2 laser were used as a transparent mold window and radiation energy so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 8 publications
0
37
0
1
Order By: Relevance
“…Sato and Kurosaki 107 and Saito et al 43 used infrared radiation for mold rapid heating and found that the birefringence in the molded part decreased with the increase in radiation intensity. Kang and coworkers 57 investigated the effects of passive heating on the birefringence distribution of an optical disk.…”
Section: Minimization Of Flow-induced Molecular Orientationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Sato and Kurosaki 107 and Saito et al 43 used infrared radiation for mold rapid heating and found that the birefringence in the molded part decreased with the increase in radiation intensity. Kang and coworkers 57 investigated the effects of passive heating on the birefringence distribution of an optical disk.…”
Section: Minimization Of Flow-induced Molecular Orientationsmentioning
confidence: 98%
“…Because of high demand of microstructured parts in the fast growing biomedical, optical, and electronics industries, this problem has received considerable attention in the past decade. Most investigations 20,21,24,34,41,43,44,47,57−61,90−93 on mold rapid heating in the past decade were aimed at providing a practical solution to this problem. A general consensus has been reached in the micromolding research community that an elevated mold temperature close to or even above the polymer solidification temperature is a necessity for successful replication of surface micro/nanostructures, particularly with high aspect ratios.…”
Section: Enhancing Replication Of Surface Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually this kind of inhomogeneity in a product has negative effects on final property. To reduce inhomogeneity in the products, separation of the filling and cooling stage in the injection molding process is the key, which means with high temperature filling and low temperature cooling in a production cycle [3]. Therefore, several techniques based on heat transfer control have been proposed to improve the quality of molded products.…”
Section: Introductionmentioning
confidence: 99%
“…This problem could be eventually solved with periodical cleaning of the mould cavity (Chang & Hwang, 2006). Direct infrared radiation heating of polymer inside the cavity has been proposed by Saito et al (2002). As long as CO 2 laser is directed towards the polymer melt through the transparent window in the mould wall, temperature gradient during injection is significantly reduced.…”
Section: Wwwintechopencommentioning
confidence: 99%